2020
DOI: 10.1097/olq.0000000000001312
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Detection of Undiagnosed HIV Within Emergency Departments in Botswana

Abstract: Among 130,161 HIV testing records from unique individuals at 149 programmatic sites in Botswana, frequency of detecting undiagnosed HIV infection within emergency departments (EDs) was 4.7% (455/9695), 2-fold higher than other clinic-based HIV counseling and testing. Men and noncitizens less frequently initiated same-day antiretroviral therapy after testing HIV positive within emergency departments. RESULTSOverall, 130,161 records from unique individuals who HIV tested in EDs (9695; 7%), VCT (12,760; 10%), or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…The proportion of newly identified PLHIV among participants completing testing was more than two-fold greater than the baseline population prevalence in the study setting (24). These data comport with prior studies in which HIV burdens among persons with injuries in Africa have been found to be greater than the prevalence in the corresponding populations (16), and that ED-based testing frequently identifies incident infections (18, 19, 37). As the current data pertaining to testing outcomes were limited, secondary to the low numbers of test offered, precise estimates on HIV burdens in the population studied are difficult to make and larger sampling frames are required.…”
Section: Discussionsupporting
confidence: 80%
“…The proportion of newly identified PLHIV among participants completing testing was more than two-fold greater than the baseline population prevalence in the study setting (24). These data comport with prior studies in which HIV burdens among persons with injuries in Africa have been found to be greater than the prevalence in the corresponding populations (16), and that ED-based testing frequently identifies incident infections (18, 19, 37). As the current data pertaining to testing outcomes were limited, secondary to the low numbers of test offered, precise estimates on HIV burdens in the population studied are difficult to make and larger sampling frames are required.…”
Section: Discussionsupporting
confidence: 80%
“…The proportion of newly identified PLHIV among participants completing testing was more than two-fold greater than the baseline population prevalence in the study setting [24]. These data comport with prior studies in which HIV burdens among persons with injuries in Africa have been found to be greater than the prevalence in the corresponding populations PLOS GLOBAL PUBLIC HEALTH [16], and that ED-based testing frequently identifies incident infections [18,19,37]. As the current data pertaining to testing outcomes were limited, secondary to the low numbers of test offered, precise estimates on HIV burdens in the population studied are difficult to make and larger sampling frames are required.…”
Section: Discussionsupporting
confidence: 72%
“…Previously undiagnosed HIV was reported in 13 studies, with a pooled prevalence of 8.8% (95% CI: 4.3–17.2; eight studies) 43 , 45 , 47 , 48 , 50 , 51 , 84 , 89 among medical patients, and 5.0% (95% CI:3.0–8.1; five studies) 37 , 44 , 65 , 68 , 72 among emergency department patients ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled prevalence of HIV in medical wards was 36.4% (95% CI: 31.3–41.8; 25 studies) 39 , 40 , 43 , 45 , 47 49 , 51 , 52 , 55 , 56 , 60 , 61 , 64 , 69 71 , 79 , 81 , 84 87 , 89 higher than the prevalence in emergency departments (21.9%; 95% CI: 14.5–31.7; seven studies). 37 , 44 , 65 , 72 , 80 , 82 , 96 HIV infection was reported using laboratory or point-of-care diagnostics in 18 studies, 37 , 40 , 43 45 , 47 51 , 56 , 65 , 68 , 72 , 82 , 84 , 89 , 96 and by medical records or clinical history in the remaining studies ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%